Optimasi Penggunaan Mutagen Kolkisin untuk Peningkatan Produktivitas Tanaman Stylo (Stylosanthes guianensis (Aubl.) Sw.): Optimalization of Colchicine Mutagen Utilization to Increase Stylo Productivity (Stylosanthes guianensis (Aubl.) Sw.) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
Colchicine is a chemical that induced mutation in plants through doubling of plant chromosomes so that polyploid plants are produced which have a larger size than diploid plants. This study aimed to determine the optimal level and soaking time of colchicine to increase the productivity of stylo plants. This study used a Completely Randomized Factorial Design (CRD) with two factors and six replications. Factor A is a the colchicine level of 0 ppm, 25 ppm, 50 ppm, 75 ppm and 100 ppm. Factor B is the soaking time of 12 hours, 24 hours and 36 hours. The variables observed were vertical height, stem diameter, leaflets length, leaflets width and number of trifoliate leaves. The results showed that the colchicine at a level of 25 ppm with soaking time of 12 hours had a significant effect (p